Pembuatan Minuman Fermentasi sebagai Upaya Peningkatan Imunitas di Masa Pandemi Covid-19 di Desa Rasau Jaya II, Kalimantan Barat - Imelda, Fenny; Rusiardy, Iwan; Purwandani, Ledy; Indrastuti, Y. Erning; Narsih, Narsih; Susana, Susana; Kuswartini, Kuswartini; Agato, Agato (LPkM Universitas Bakrie, 2022)
This Community Service Activity (PPM) collaborates with the Family Welfare Empowerment (PKK) of Rasau Jaya II Village as a partner. Partners have not used local food, namely sweet corn and sweet potatoes, into fermented beverage products that can increase immunity during the Covid-19 pandemic. It is necessary to increase the mindset of partners in utilizing local food ingredients as strategic potentials in an effort to increase family immunity, science and technology insights, skills and expertise of partners. The purpose of this PPM activity is to increase the insight, understanding, and awareness of partners regarding preventive efforts during the pandemic by increasing immunity through the consumption of local food. In addition, providing science and technology transfer in the form of appropriate technology (TTG) for processing fermented drinks as an effort to increase the added value of local food ingredients through diversification of their processed products. The implementation method in achieving goals and targets is in the form of socializing information on local potential, science and technology, and preventive efforts during the Covid-19 pandemic, transferring science and technology in the form of TTG training in processing fermented drinks, and conducting monitoring and evaluation. The results of the activity are increased insight and understanding of community groups about local food ingredients as a source of fibre, prebiotics, and probiotics; increasing awareness of community groups regarding preventive efforts during the pandemic by increasing immunity through consumption of local food; increased skills of community groups after simple TTG training in fermented beverage processing, and increasing the added value of local food ingredients through diversification of their processed products into fermented drinks.